Staff supported parental involvement in effective early interventions for at-risk children – a systematic research review: VIDA research series 2013:01 - Larsen, Michael Søgaard; Holm, Anders; Jensen, Bente; Plough, Niels; Berliner, Peter (AU Library Scholarly Publishing Services, 2015)
The article presents a review of international research on the effect of early interventions with parental involvement. Ten international and national databases were searched. Hits were supplemented with references from the review group. The search process found 1933 unique references, which were subsequently screened for relevance. Seventy-eight references, which reported on 27 different studies, were relevant for the conceptual focus of the mapping. These 27 studies were re-described and data were extracted from them. They were also examined for evidence weight (high, medium, low) in a double peer review system. Thirteen interventions with evidence-based positive effects on the cognitive, emotional, and social development of the children were identified. The interventions were then described in terms of curriculum, theoretical framework, empirical basis, and methods of parental involvement. The study shows that parents are involved through a variety of activities, which include: (1) educators visit the homes and provide guidance for parents and their children there; (2) parents conduct specific activities with the children at home and or in the institution; (3) parents participate in activities with other parents, and (4) parents participate in activities with the group of children in the day care center. Only four studies (examining three interventions) of the 13 studies investigate the effect of parental involvement in particular. Thus, it cannot be concluded that parental involvement is a decisive factor for the positive effects in the remaining ten interventions. However, the review shows that parental involvement, when day care center staff or other facilitators assist the parents, seems to have a positive effect when combined with an intervention in the day care center.